(untitled) (Journal of Oriental Studies, 2016)
energy is a very important tool for strengthening of turkey not only in economic but also in international geopolitics. the most significant condition for boosting economy of turkey is to secure new energy sources and strategies.. trying to avoid to become totally depended on russia`s energy deliveries, turkey is urged to implement new and alternative energy logistic projects. these energy projects comprise such projects like taNaP, bТЕ, Nabucco, taP, trans-Caspian pipeline.